Cerebello‐Prefrontal Connectivity Underlying Cognitive Dysfunction in Spinocerebellar Ataxia Type 2 - Ami Kumar; Ruo‐Yah Lai; Zena Fadel; Yicheng Lin; Pia Parekh; Rachel Griep; Ming‐Kai Pan; Sheng‐Han Kuo (Annals of Clinical and Translational Neurology)
ABSTRACT Objective Spinocerebellar ataxia type 2 (SCA2) is a hereditary cerebellar degenerative disorder, with motor and cognitive symptoms. The constellation of cognitive symptoms due to cerebellar degeneration is named cerebellar cognitive affective syndrome (CCAS), which has increasingly been recognized to profoundly impact patients' quality of life; however, the brain circuits underlying these cognitive dysfunctions remain elusive. Methods We utilized a novel technique, cerebello‐cortical electroencephalogram (EEG), to investigate the resting‐state functional connectivity in different frequency domains in 12 SCA2 patients and 24 age‐matched controls. Given that the prefrontal cortex is strongly connected to the cerebellum, we studied the EEG connectivity between the cerebellum and the prefrontal cortex. We also conducted correlation analyses to explore the association between this connectivity and the severity of cognitive dysfunction, determined by CCAS scores. Results Source‐space spectral analysis differences between SCA2 patients and controls were observed in the cerebellum at the delta, theta, and beta frequencies. Functional connectivity between the posterior cerebellum and the prefrontal cortex revealed decreased theta and increased beta connectivity in SCA2 patients, with no differences in delta connectivity. Increased beta connectivity was unique to the prefrontal regions, not seen in the connectivity to the primary motor cortex or mid‐temporal lobe. Interestingly, this beta connectivity correlated with CCAS scores in SCA2 patients. Conclusion Our findings demonstrated that SCA2 patients have an increase in beta cerebello‐prefrontal connectivity that correlates with cognitive performance. These findings suggest cerebello‐cortical EEG could track circuit dysfunction underlying cognitive symptoms in SCA2, paving the way for developing targeted neuromodulation therapeutics.